Decision Support System for Determining Employee Leave Using the Moora Method Case Study of the Central Bureau of Statistics of Medan City - Qawakib, Cahayati Annisa; Wahyuni, Dewi; Imam, Chairul (Journal of Technology and Computer, 2024)
Data is indispensable in the decision-making system process. Good and appropriate decisions require accurate, fast, and relevant data. The decision support system for determining employee leave at the Central Bureau of Statistics of Medan City still uses a simple method that is only considered by the general subdivision and its leadership without following the existing criteria standards, which is very inefficient for employees who have to wait for leave approval from their leaders. The method used in this decision support system for determining employee leave is the Multi-Objective Optimisation On The Basis Of Ratio Analysis (MOORA) method and system development using the waterfall model. In implementing and designing the program using the Hypertext Preprocessor (PHP) programming language with the database used MySQL. The final results obtained from this research are A8 on behalf of Rabiah with the highest rank with a value of 0.2913 and A2 on behalf of Artha with the lowest rank with a value of 0,1338.